Kano 모델을 이용한 설비시공회사의 CRM이 고객만족도에 미치는 영향 - 이승호; Seung Ho Lee; 장석주; Seog Ju Chang (品質經營學會誌, 2017)
Purpose: This study investigates the effect of CRM activities of Korean equipment construction companies on the quality satisfaction perceived by consumers as an analysis method using Kano model. Methods: It use the Kano model to classify the quality characteristics of the CRM activities of equipment construction companies, focusing on consumer perception, and analyze the effect on the level of quality satisfaction perceived by consumers. Results: The results showed that most of quality attributes of CRM activities in the equipment companies were categorized as ‘one-dimensional’ quality. Conclusion: The CRM activities in equipment construction compaies is verified to be essential component of successful strategy to improve customer’s satisfaction.